Investigation of the Serotonin, Cortisol Hormones and some Biochemical Parameters in Patients with Beta Thalassemia in Thi-Qar Governorate /Iraq - alazraqi, noor; Leila Sadeghi; Gholamreza Dehghan (University of Thi-Qar Journal of Science, 2024)
Beta thalassemia (β-thalassemia) is the most severe kind of β-thalassemia hereditary disease that makes blood transfusion dependent. Patients with β-thalassemia disease experience many physiological abnormalities, including oxidative stress, iron overload, and aggregated β-globin proteins. These abnormalities may also lead to premature RBC mortality. In the present study, 100 patients with β-thalassemia major with an average age of 16.30 ± 6.67 years old and 30 healthy controls with an average age of 14.63 ± 4.17 years old were included in this study. The serum levels of urea, creatinine, serotonin, and cortisol were investigated in the patient and control groups. The results showed a marked increase in the urea levels among the patients compared to the control group (from 14.63 ± 6.05 mg/dl in the control group to 24.98 ± 11.35 mg/dl in patient group) with P <0.001, rendering this change highly statistically significant. While there was a noticeable increase in creatinine levels between patients and controls (from 0.387 ± 0.199 mg/dl in the control group to 0.466 ± 0.208 mg/dl in the patient group. Statistical analysis revealed this change with non-significance of P = 0.066. Furthermore, the obtained results indicated that the serum level of serotonin decreased in patient group (from 393.46 ± 192.42 ng/ml in control group to 385.63 ± 167.70 ng/ml in patient group) with P=0.884, while β-thalassemia major subjects showed a significantly higher level of cortisol compared to the healthy control group (from 94.97 ± 67.56 ng/ml in control group